Geochemical impacts of oxygen impurities on subsurface biomethane storage - Zaid Jangda; Lorraine Boak; Robbie Skivington; Hunter Keil; Ali Daoud; Martin J. Maple; Andreas Busch (Gas Science and Engineering, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Phenotypic and genotypic antimicrobial susceptibility of non-aureus staphylococci in dairy goats - Michelle P. Buckley; Fazal Sattar; Ganwu Li; Orhan Sahin; Roselle C. Busch; Amanda J. Kreuder; Paul J. Plummer; Patrick J. Gorden (Small Ruminant Research, 2025)

OS02-04 From Toxicogenomics Data to Cumulative Assessment Groups: A Framework for Chemical Grouping - S. Canzler; J. Lehmann; J. Schor; W. Busch; G. Iacono; J. Hackermüller (Toxicology Letters, 2025)

OS01-11 Development of a Human Intestinal Stem Cell-Derived 2D Monolayer Model for Transport and Metabolism Studies - J. Wang; T. Walraven; M. Busch; H. Bouwmeester; N. Kramer (Toxicology Letters, 2025)

Efficacy of two long-acting intramammary antimicrobials for curing subclinical mastitis due to non-aureus staphylococci in dairy goats - Michelle P. Buckley; Gustavo S. Silva; Roselle C. Busch; Orhan Sahin; Paul J. Plummer; Patrick J. Gorden (Small Ruminant Research, 2025)

Sponge species from New Zealand may transform and degrade dissolved organic matter - Tanja Stratmann; Mario L.M. Miranda; Anna de Kluijver; Kathrin Busch; Michelle Kelly; Sadie Mills; Peter J. Schupp (Journal of Experimental Marine Biology and Ecology, 2025)

Population genetic structure in two contrasting human-altered environments of yellow pygmy rice rat Oligoryzomys flavescens - E. Muschetto; I. E. Gómez Villafañe; M. Scaltritti; J. Fraschina; V. León; L. Adduci; D. Hancke; S. Guidobono; G. R. Cueto; M. A. Tripodi; E. Hasson; M. Busch; et al. (Oecologia, 2025)

Nutrient fluxes, oxygen consumption and fatty acid composition from deep-water demo- and hexactinellid sponges from New Zealand - Tanja Stratmann; Kathrin Busch; Anna de Kluijver; Michelle Kelly; Sadie Mills; Sven Rossel; Peter J. Schupp (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Semi-structured citizen science data reveal mixed effectiveness of EU Special Protection Areas (SPA) in Germany - F.J. Pflüger; C. Frank; M. Busch; J. Wahl; R. Dröschmeister; C. Sudfeldt; J. Kamp (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A novel in vitro high-content imaging assay for the prediction of drug-induced lung toxicity - Paul A. Fitzpatrick; Julia Johansson; Gareth Maglennon; Ian Wallace; Ramon Hendrickx; Marianna Stamou; Kinga Balogh Sivars; Susann Busch; Linnea Johansson; Natalie Van Zuydam; Kelley Patten; Per M. Åberg; et al. (Archives of Toxicology, 2024)
The development of inhaled drugs for respiratory diseases is frequently impacted by lung pathology in non-clinical safety studies. To enable design of novel candidate drugs with the right safety profile, predictive in vitro lung toxicity assays are required that can be applied during drug discovery for early hazard identification and mitigation. Here, we describe a novel high-content imaging-based screening assay that allows for quantification of the tight junction protein occludin in A549 cells, as a model for lung epithelial barrier integrity. We assessed a set of compounds with a known lung safety profile, defined by clinical safety or non-clinical in vivo toxicology data, and were able to correctly identify 9 of 10 compounds with a respiratory safety risk and 9 of 9 compounds without a respiratory safety risk (90% sensitivity, 100% specificity). The assay was sensitive at relevant compound concentrations to influence medicinal chemistry optimization programs and, with an accessible cell model in a 96-well plate format, short protocol and application of automated imaging analysis algorithms, this assay can be readily integrated in routine discovery safety screening to identify and mitigate respiratory toxicity early during drug discovery. Interestingly, when we applied physiologically-based pharmacokinetic (PBPK) modelling to predict epithelial lining fluid exposures of the respiratory tract after inhalation, we found a robust correlation between in vitro occludin assay data and lung pathology in vivo, suggesting the assay can inform translational risk assessment for inhaled small molecules.

Investigating the suitability of online flow cytometry for monitoring full-scale drinking water ozone system disinfection effectiveness - Katherine S. Dowdell; Kirk Olsen; Ernesto F. Martinez Paz; Aini Sun; Jeff Keown; Rebecca Lahr; Brian Steglitz; Andrea Busch; John J. LiPuma; Terese Olson; Lutgarde Raskin (Water Research, 2024)

Adverse effects of crushed seafloor massive sulphide deposits on the boreal deep-sea sponge Geodia barretti Bowerbank, 1858 and its associated fauna - Erik Wurz; Linn M.Brekke Olsen; Kathrin Busch; Tone Ulvatn; Hans T. Rapp; Ronald Osinga; Albertinka J. Murk (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Entanglement and ingestion of microfibers by the oyster pea crab Zaops ostreum, an endosymbiont of the eastern oyster Crassostrea virginica - Linda J. Walters; Sidney J. Busch; Sophia Vermeulen; Casey A. Craig (Marine Pollution Bulletin, 2024)

A novel climate and health decision support platform: Approach, outputs, and policy considerations - Jeremy J. Hess; Timothy J. Sheehan; Alyssa Miller; Rad Cunningham; Nicole A. Errett; Tania Busch Isaksen; Jason Vogel; Kristie L. Ebi (Environmental Research, 2023)

Low rate of detection of SARS-CoV-2 RNA in deceased tissue donors - Melissa A. Greenwald; Eduard Grebe; Valerie Green; Alyce Linthurst Jones; Jeffrey M. Linnen; Phillip Williamson; Michael P. Busch; Matthew J. Kuehnert (Cell and Tissue Banking, 2023)
Given the possibility for disease transmission, this study was performed to determine whether there is detectable SARS-CoV-2 viral RNA in the blood of deceased tissue donors. A retrospective analysis of blood samples from eligible deceased tissue donors from Oct 2019 through June 2020 was performed. Plasma aliquots were initially tested with a SARS-CoV-2 NAT Assay; positive samples were further tested using an alternate NAT and an antibody assay. The proportion of donors with confirmed RNAemia and 95% confidence intervals were computed. Of donor samples collected in 2019, 894 yielded valid results, with 6 initially positive, none of which confirmed positive by alternate NAT. Of donor samples collected in 2020, 2562 yielded valid initial NAT results, with 21 (0.8%) initially positive. Among those, 3 were confirmed by alternate NAT, 17 were not confirmed, and 1 had an invalid alternate NAT result. The rate of SARS-CoV-2 RNAemia in deceased tissue donors is approximately 1 per 1000, and it is unknown whether this RNAemia reflects the presence of infectious virus. Given these results, the risk of transmission through tissue is thought likely to be low.

The AFB1 auxin receptor controls the cytoplasmic auxin response pathway in Arabidopsis thaliana - Shiv Mani Dubey; Soeun Han; Nathan Stutzman; Michael J. Prigge; Eva Medvecká; Matthieu Pierre Platre; Wolfgang Busch; Matyáš Fendrych; Mark Estelle (Molecular Plant, 2023)

Indicators of water use efficiency across diverse agroecosystems and spatiotemporal scales - David L. Hoover; Lori J. Abendroth; Dawn M. Browning; Amartya Saha; Keirith Snyder; Pradeep Wagle; Lindsey Witthaus; Claire Baffaut; Joel A. Biederman; David D. Bosch; Rosvel Bracho; Dennis Busch; et al. (Science of The Total Environment, 2023)

Evaluating environmental controls on the exoskeleton density of larval Dungeness crab via micro computed tomography - Casey P. Saenger; Paul McElhany; Emily L. Norton; D. Shallin Busch; Samantha A. Siedlecki; Simone R. Alin; Richard A. Feely; Albert J. Hermann; Nina Bednaršek (Frontiers in Marine Science, 2023)
Dungeness crab ( Metacarcinus magister ) have significant socioeconomic value, but are threatened by ocean acidification (OA) and other environmental stressors that are driven by climate change. Despite evidence that adult harvests are sensitive to the abundance of larval populations, relatively little is known about how Dungeness megalopae will respond to these stressors. Here we evaluate the ability to use micro-computed tomography (μCT) to detect variations in megalope exoskeleton density and how these measurements reflect environmental variables and calcification mechanisms. We use a combination of field data, culture experiments, and model simulations to suggest resolvable differences in density are best explained by minimum pH at the time zoeae molt into megalopae. We suggest that this occurs because more energy must be expended on active ion pumping to reach a given degree of calcite supersaturation at lower pH. Energy availability may also be reduced due to its diversion to other coping mechanisms. Alternate models based on minimum temperature at the time of the zoea-megalope molt are nearly as strong and complicate the ability to conclusively disentangle pH and temperature influences. Despite this, our results suggest that carryover effects between life stages and short-lived extreme events may be particularly important controls on exoskeleton integrity. μCT-based estimates of exoskeleton density are a promising tool for evaluating the health of Dungeness crab populations that will likely provide more nuanced information than presence-absence observations, but future in situ field sampling and culture experiments are needed to refine and validate our results.

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Nearshore Dissolved and Particulate Organic Matter Dynamics in the Southwestern Baltic Sea: Environmental Drivers and Time Series Analysis (2010–2020) - Helena Osterholz; Christian Burmeister; Susanne Busch; Madleen Dierken; Helena C. Frazão; Regina Hansen; Jenny Jeschek; Anke Kremp; Lars Kreuzer; Birgit Sadkowiak; Joanna J. Waniek; Detlef E. Schulz-Bull (Frontiers in Marine Science, 2021)
Dissolved and particulate organic carbon (DOC, POC) and nitrogen (DON, PON) constitute essential nutrient and energy sources to heterotrophic microbes in aquatic systems. Especially in the shallow coastal ocean, the concentrations are highly variable on short timescales, and cycling is heavily affected by different sources and environmental drivers. We analyzed surface water organic carbon and nitrogen concentrations determined weekly from 2010 to 2020 in the nearshore southwestern Baltic Sea (Heiligendamm, Germany) in relation to physical, chemical and biological parameters available since 1988. Mixing of low-DOC North Sea water with high-DOC Baltic Sea water, as well as in situ primary production, were confirmed as the main drivers of organic carbon and nitrogen concentrations. Tight coupling between POC, PON, chlorophyll a and phytoplankton carbon with DON seasonal dynamics corroborated the close relationship between phytoplankton production and degradation of organic nutrients with preferential remineralization of nitrogen. Significant changes in air and water temperature, salinity, and inorganic nutrients over time indicated effects of climate change and improved water quality management in the eutrophic Baltic Sea. Bulk organic nutrient concentrations did not change over time, while the salinity-corrected fraction of the DOC increased by about 0.6 μmol L –1 yr –1 . Concurrently, chlorophyll a and Bacillariophyceae and Cryptophyceae carbon increased, denoting a potential link to primary productivity. The high variability of the shallow system exacerbates the detection of trends, but our results emphasize the value of these extended samplings to understand coupled biogeochemical cycling of organic matter fractions and to detect trends in these important carbon reservoirs.

Evaluation of Cardiotonic Steroid Modulation of Cellular Cholesterol and Phospholipid - Lilian N. D. Silva; Israel J. P. Garcia; Jessica M. M. Valadares; Marco Tulio C. Pessoa; Marina Marques Toledo; Matheus V. Machado; Mileane Souza Busch; Isabella Rocha; José Augusto F. P. Villar; Georgia C. Atella; Herica L. Santos; Vanessa F. Cortes; et al. (The Journal of Membrane Biology, 2021)

Marine Citizen Science: Current State in Europe and New Technological Developments - Carlos Garcia-Soto; Jan J. C. Seys; Oliver Zielinski; J. A. Busch; S. I. Luna; Jose Carlos Baez; C. Domegan; K. Dubsky; I. Kotynska-Zielinska; P. Loubat; Francesca Malfatti; G. Mannaerts; et al. (Frontiers in Marine Science, 2021)
Marine citizen science is emerging with promising opportunities for science, policy and public but there is still no comprehensive overview of the current state in Europe. Based on 127 projects identified for the North Sea area we estimate there might be as much as 500 marine and coastal citizen science projects running in Europe, i.e., one marine citizen science project per ∼85 km of coastline, with an exponential growth since 1990. Beach-based projects are more accessible and hence most popular (60% of the projects), and the mean duration of the projects is 18–20 years. Current trends, topics, organizers, aims, and types of programme in terms of participation are presented in this overview. Progress in marine citizen science is specially enabled and promoted through technological developments. Recent technological advances and best practise examples are provided here, untapping the potential of smart mobile apps, do-it-yourself (DIY) technologies, drones, and artificial intelligence (AI) web services.

Development of an AAV9-RNAi-mediated silencing strategy to abrogate TRPM4 expression in the adult heart - Rebekka Medert; Andreas Jungmann; Staffan Hildebrand; Martin Busch; Dirk Grimm; Veit Flockerzi; Oliver J. Müller; Patrick Most; Dagmar Schumacher; Marc Freichel (Pflügers Archiv - European Journal of Physiology, 2021)
The cation channel transient receptor potential melastatin 4 (TRPM4) is a calcium-activated non-selective cation channel and acts in cardiomyocytes as a negative modulator of the L-type Ca 2+ influx. Global deletion of TRPM4 in the mouse led to increased cardiac contractility under β-adrenergic stimulation. Consequently, cardiomyocyte-specific inactivation of the TRPM4 function appears to be a promising strategy to improve cardiac contractility in heart failure patients. The aim of this study was to develop a gene therapy approach in mice that specifically silences the expression of TRPM4 in cardiomyocytes. First, short hairpin RNA miR30 (shRNA miR30 ) sequences against the TRPM4 mRNA were screened in vitro using lentiviral transduction for a stable expression of the shRNA cassettes. Western blot analysis identified three efficient shRNA miR30 sequences out of six, which reduced the endogenous TRPM4 protein level by up to 90 ± 6%. Subsequently, the most efficient shRNA miR30 sequences were delivered into cardiomyocytes of adult mice using adeno-associated virus serotype 9 (AAV9)-mediated gene transfer. Initially, the AAV9 vector particles were administered via the lateral tail vein, which resulted in a downregulation of TRPM4 by 46 ± 2%. Next, various optimization steps were carried out to improve knockdown efficiency in vivo. First, the design of the expression cassette was streamlined for integration in a self-complementary AAV vector backbone for a faster expression. Compared to the application via the lateral tail vein, intravenous application via the retro-orbital sinus has the advantage that the vector solution reaches the heart directly and in a high concentration, and eventually a TRPM4 knockdown efficiency of 90 ± 7% in the heart was accomplished by this approach. By optimization of the shRNA miR30 constructs and expression cassette as well as the route of AAV9 vector application, a 90% reduction of TRPM4 expression was achieved in the adult mouse heart. In the future, AAV9-RNAi-mediated inactivation of TRPM4 could be a promising strategy to increase cardiac contractility in preclinical animal models of acute and chronic forms of cardiac contractile failure.

Westward range expansion from middle latitudes explains the Mississippi River discontinuity in a forest herb of eastern North America - Carly J. Prior; Nathan C. Layman; Matthew H. Koski; Laura F. Galloway; Jeremiah W. Busch (Molecular Ecology, 2020)
It is often expected that temperate plants have expanded their geographical ranges northward from primarily southern refugia. Evidence for this hypothesis is mixed in eastern North American species, and there is increasing support for colonization from middle latitudes. We studied genome‐wide patterns of variation in RADseq loci to test hypotheses concerning range expansion in a North American forest herb ( Campanula americana ). First, spatial patterns of genetic differentiation were determined. Then phylogenetic relationships and divergence times were estimated. Spatial signatures of genetic drift were also studied to identify the directionality of recent range expansion and its geographical origins. Finally, spatially explicit scenarios for the spread of plants across the landscape were compared, using variation in the population mutation parameter and Tajima's D . We found strong longitudinal subdivision, with populations clustering into groups west and east of the Mississippi River. While the southeastern region was probably part of a diverse Pleistocene refugium, there is little evidence that range expansion involved founders from these southern locales. Instead, declines in genetic diversity and the loss of rare alleles support a westward colonization wave from a middle latitude refugium near the southern Appalachian Mountains, with subsequent expansion from a Pleistocene staging ground in the Mississippi River Valley (0.51–1.27 million years ago). These analyses implicate stepping stone colonization from middle latitudes as an important mechanism of species range expansion in eastern North America. This study further demonstrates the utility of population genetics as a tool to infer the routes travelled by organisms during geographical range expansion.

Risks of ocean acidification in the California Current food web and fisheries: ecosystem model projections - Kristin N. Marshall; Isaac C. Kaplan; Emma E. Hodgson; Albert Hermann; D. Shallin Busch; Paul McElhany; Timothy E. Essington; Chris J. Harvey; Elizabeth A. Fulton (Global Change Biology, 2017)
The benefits and ecosystem services that humans derive from the oceans are threatened by numerous global change stressors, one of which is ocean acidification. Here, we describe the effects of ocean acidification on an upwelling system that already experiences inherently low pH conditions, the California Current. We used an end‐to‐end ecosystem model (Atlantis), forced by downscaled global climate models and informed by a meta‐analysis of the pH sensitivities of local taxa, to investigate the direct and indirect effects of future pH on biomass and fisheries revenues. Our model projects a 0.2‐unit drop in pH during the summer upwelling season from 2013 to 2063, which results in wide‐ranging magnitudes of effects across guilds and functional groups. The most dramatic direct effects of future pH may be expected on epibenthic invertebrates (crabs, shrimps, benthic grazers, benthic detritivores, bivalves), and strong indirect effects expected on some demersal fish, sharks, and epibenthic invertebrates (Dungeness crab) because they consume species known to be sensitive to changing pH . The model's pelagic community, including marine mammals and seabirds, was much less influenced by future pH . Some functional groups were less affected to changing pH in the model than might be expected from experimental studies in the empirical literature due to high population productivity (e.g., copepods, pteropods). Model results suggest strong effects of reduced pH on nearshore state‐managed invertebrate fisheries, but modest effects on the groundfish fishery because individual groundfish species exhibited diverse responses to changing pH . Our results provide a set of projections that generally support and build upon previous findings and set the stage for hypotheses to guide future modeling and experimental analysis on the effects of OA on marine ecosystems and fisheries.

The association of children’s mathematic abilities with both adults’ cognitive abilities and intrinsic fronto-parietal networks is altered in preterm-born individuals - J. G. Bäuml; C. Meng; M. Daamen; N. Baumann; B. Busch; P. Bartmann; D. Wolke; H. Boecker; A. Wohlschläger; C. Sorg; Julia Jaekel (Brain Structure and Function, 2017)

Efficient genome editing of differentiated renal epithelial cells - Alexis Hofherr; Tilman Busch; Nora Huber; Andreas Nold; Albert Bohn; Amandine Viau; Frank Bienaimé; E. Wolfgang Kuehn; Sebastian J. Arnold; Michael Köttgen (Pflügers Archiv - European Journal of Physiology, 2017)

Extensive and interrelated subcortical white and gray matter alterations in preterm-born adults - C. Meng; J. G. Bäuml; M. Daamen; J. Jaekel; J. Neitzel; L. Scheef; B. Busch; N. Baumann; H. Boecker; C. Zimmer; P. Bartmann; D. Wolke; et al. (Brain Structure and Function, 2016)

Using Uncertain Climate and Development Information in Health Adaptation Planning - Kristie L. Ebi; Jeremy J. Hess; Tania Busch Isaksen (Current Environmental Health Reports, 2016)

Atlantic salmon, S almo salar L . are broadly susceptible to isolates representing the N orth A merican genogroups of infectious hematopoietic necrosis virus - G Kurath; J R Winton; O B Dale; M K Purcell; K Falk; R A Busch (Journal of Fish Diseases, 2016)
Beginning in 1992, three epidemic waves of infectious hematopoietic necrosis, often with high mortality, occurred in farmed A tlantic salmon S almo salar L . on the west coast of N orth A merica. We compared the virulence of eleven strains of infectious hematopoietic necrosis virus ( IHNV ), representing the U , M and L genogroups, in experimental challenges of juvenile A tlantic salmon in freshwater. All strains caused mortality and there was wide variation within genogroups: cumulative mortality for five U ‐group strains ranged from 20 to 100%, four M ‐group strains ranged 30‐63% and two L ‐group strains varied from 41 to 81%. Thus, unlike P acific salmonids, there was no apparent correlation of virulence in a particular host species with virus genogroup. The mortality patterns indicated two different phenotypes in terms of kinetics of disease progression and final per cent mortality, with nine strains having moderate virulence and two strains (from the U and L genogroups) having high virulence. These phenotypes were investigated by histopathology and immunohistochemistry to describe the variation in the course of IHNV disease in A tlantic salmon. The results from this study demonstrate that IHNV may become a major threat to farmed A tlantic salmon in other regions of the world where the virus has been, or may be, introduced.

Opportunities and Challenges in the Design and Analysis of Biomass Supply Chains - Pasi T. Lautala; Michael R. Hilliard; Erin Webb; Ingrid Busch; J. Richard Hess; Mohammad S. Roni; Jorge Hilbert; Robert M. Handler; Roger Bittencourt; Amir Valente; Tuuli Laitinen (Environmental Management, 2015)

Development of a new LAMP assay for the detection of CSFV strains from Cuba: a proof-of-concept study - Alexander Postel; Lester J. Pérez; Carmen L. Perera; Stefanie Schmeiser; Denise Meyer; Alexandra Meindl-Boehmer; Liliam Rios; Sophia Austermann-Busch; Maria T. Frias-Lepoureau; Paul Becher (Archives of Virology, 2015)

Erratum to: Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Invasion of Bromus tectorum (L.) into California and the American Southwest: rapid, multi-directional and genetically diverse - Angela R. Pawlak; Richard N. Mack; Jeremiah W. Busch; Stephen J. Novak (Biological Invasions, 2015)

Method Transfer, Partial Validation, and Cross Validation: Recommendations for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Team - R. J. Briggs; R. Nicholson; F. Vazvaei; J. Busch; M. Mabuchi; K. S. Mahesh; M. Brudny-Kloeppel; N. Weng; P. A. R. Galvinas; P. Duchene; Pei Hu; R. W. Abbott (The AAPS Journal, 2014)

Maternal coding variants in complement receptor 1 and spontaneous idiopathic preterm birth - Jude J. McElroy; Courtney E. Gutman; Christian M. Shaffer; Tamara D. Busch; Hilkka Puttonen; Kari Teramo; Jeffrey C. Murray; Mikko Hallman; Louis J. Muglia (Human Genetics, 2013)

Oxygen minimum zones harbour novel viral communities with low diversity - Noriko Cassman; Alejandra Prieto‐Davó; Kevin Walsh; Genivaldo G. Z. Silva; Florent Angly; Sajia Akhter; Katie Barott; Julia Busch; Tracey McDole; J. Matthew Haggerty; Dana Willner; Gadiel Alarcón; et al. (Environmental Microbiology, 2012)
Summary Oxygen minimum zones ( OMZs ) are oceanographic features that affect ocean productivity and biodiversity, and contribute to ocean nitrogen loss and greenhouse gas emissions. Here we describe the viral communities associated with the E astern T ropical S outh P acific ( ETSP ) OMZ off I quique, C hile for the first time through abundance estimates and viral metagenomic analysis. The viral‐to‐microbial ratio ( VMR ) in the ETSP OMZ fluctuated in the oxycline and declined in the anoxic core to below one on several occasions. The number of viral genotypes (unique genomes as defined by sequence assembly) ranged from 2040 at the surface to 98 in the oxycline, which is the lowest viral diversity recorded to date in the ocean. Within the ETSP OMZ viromes, only 4.95% of genotypes were shared between surface and anoxic core viromes using reciprocal BLASTn sequence comparison. ETSP virome comparison with surface marine viromes ( S argasso S ea, G ulf of M exico, K ingman R eef, C hesapeake B ay) revealed a dissimilarity of ETSP OMZ viruses to those from other oceanic regions. From the 1.4 million non‐redundant DNA sequences sampled within the altered oxygen conditions of the ETSP OMZ , more than 97.8% were novel. Of the average 3.2% of sequences that showed similarity to the SEED non‐redundant database, phage sequences dominated the surface viromes, eukaryotic virus sequences dominated the oxycline viromes, and phage sequences dominated the anoxic core viromes. The viral community of the ETSP OMZ was characterized by fluctuations in abundance, taxa and diversity across the oxygen gradient. The ecological significance of these changes was difficult to predict; however, it appears that the reduction in oxygen coincides with an increased shedding of eukaryotic viruses in the oxycline, and a shift to unique viral genotypes in the anoxic core.

Narrow species concepts in the Frullania dilatata–appalachiana–eboracensis complex (Porellales, Jungermanniopsida): evidence from nuclear and chloroplast DNA markers - A. Bombosch; A. Wieneke; A. Busch; R. Jonas; J. Hentschel; H.-P. Kreier; B. Shaw; A. J. Shaw; J. Heinrichs (Plant Systematics and Evolution, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Detecting marine hazardous substances and organisms: sensors for pollutants, toxins, and pathogens - O. Zielinski; J. A. Busch; A. D. Cembella; K. L. Daly; J. Engelbrektsson; A. K. Hannides; H. Schmidt (Ocean Science, 2009)
Marine environments are influenced by a wide diversity of anthropogenic and natural substances and organisms that may have adverse effects on human health and ecosystems. Real-time measurements of pollutants, toxins, and pathogens across a range of spatial scales are required to adequately monitor these hazards, manage the consequences, and to understand the processes governing their magnitude and distribution. Significant technological advancements have been made in recent years for the detection and analysis of such marine hazards. In particular, sensors deployed on a variety of mobile and fixed-point observing platforms provide a valuable means to assess hazards. In this review, we present state-of-the-art of sensor technology for the detection of harmful substances and organisms in the ocean. Sensors are classified by their adaptability to various platforms, addressing large, intermediate, or small areal scales. Current gaps and future demands are identified with an indication of the urgent need for new sensors to detect marine hazards at all scales in autonomous real-time mode. Progress in sensor technology is expected to depend on the development of small-scale sensor technologies with a high sensitivity and specificity towards target analytes or organisms. However, deployable systems must comply with platform requirements as these interconnect the three areal scales. Future developments will include the integration of existing methods into complex and operational sensing systems for a comprehensive strategy for long-term monitoring. The combination of sensor techniques on all scales will remain crucial for the demand of large spatial and temporal coverage.

Characterization of expressed class II MHC sequences in the banner-tailed kangaroo rat (Dipodomys spectabilis) reveals multiple DRB loci - Joseph D. Busch; Peter M. Waser; J. Andrew DeWoody (Immunogenetics, 2008)

Recent demographic bottlenecks are not accompanied by a genetic signature in banner‐tailed kangaroo rats ( Dipodomys spectabilis ) - JOSEPH D. BUSCH; PETER M. WASER; J. ANDREW DeWOODY (Molecular Ecology, 2007)
Single‐sample methods of bottleneck detection are now routine analyses in studies of wild populations and conservation genetics. Three common approaches to bottleneck detection are the heterozygosity excess, mode‐shift, and M‐ ratio tests. Empirical groundtruthing of these methods is difficult, but their performances are critical for the accurate reconstruction of population demography. We use two banner‐tailed kangaroo rat ( Dipodomys spectabilis ) populations from southeastern Arizona (USA) that are known to have experienced recent demographic reductions to search for genetic bottleneck signals with eight microsatellite loci. Over eight total sample‐years, neither population showed a genetic bottleneck signature. M ‐ratios in both populations were large, stable, and never fell below a critical significance value ( M c ). The mode shift test did not detect any distortion of allele frequencies, and tests of heterozygosity excess were not significant in postbottleneck samples when we used standard microsatellite mutation models. The genetic effects of bottlenecks like those experienced by our study populations should be strongly influenced by rates of mutation and migration. We used genetic parentage data to estimate a relatively high mutation rate in D. spectabilis (0.0081 mutants/generation/locus), but mutation alone is unlikely to explain the temporal distribution of rare alleles that we observed. Migration (gene flow) is a more likely explanation, despite prior mark–recapture analysis that estimated very low rates of interpopulation dispersal. We interpret our kangaroo rat data in light of the broader literature and conclude that in natural populations connected by dispersal, demographic bottlenecks may prove difficult to detect using molecular genetic data.

Parentage analysis detects cryptic precapture dispersal in a philopatric rodent - PETER M. WASER; JOSEPH D. BUSCH; CORY R. McCORMICK; J. ANDREW DEWOODY (Molecular Ecology, 2006)
Locating birthplaces using genetic parentage determination can increase the precision and accuracy with which animal dispersal patterns are established. We re‐analyse patterns of movement away from the birthplace as a function of time, sex and population density for a sample of 303 banner‐tailed kangaroo rats, Dipodomys spectabilis. We located birth sites using a combination of likelihood‐based parentage analysis with live‐trapping of mothers during the breeding season. The results demonstrate that natal‐breeding site distances are density dependent in this species; in particular, both sexes emigrate earlier in the year, and females disperse farther than males, at low population densities. Banner‐tailed kangaroo rats were chosen as a study system because live‐trapping easily detects maternal and offspring locations; nevertheless, parentage analysis reveals that some offspring evade early detection and move substantial distances before their first capture. In a few cases, the approach even detects dispersal out of the natal ‘deme’ prior to first capture. Parentage analysis confirms the extreme philopatry of both sexes but indicates that prior estimates of median dispersal distance were too low. For D. spectabilis , more accurate location of individual birthplaces clarifies patterns of sex bias and density dependence in dispersal, and may resolve apparent discrepancies between direct and indirect estimates of dispersal distance. For species in which mothers can be more reliably trapped than juveniles, using offspring genotypes to locate parents is a novel way that genetic techniques can contribute to the analysis of animal dispersal.

Effects of the atrial antiarrhythmic drug AVE0118 on cardiac ion channels - Heinz Ggelein; J. Brendel; K. Steinmeyer; C. Strbing; N. Picard; D. Rampe; K. Kopp; A.E. Busch; M. Bleich (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Granulocyte colony-stimulating factor (G-CSF) reduces not only gram-negative but also gram-positive infection-associated proinflammatory cytokine release by interaction between Kupffer cells and leukocytes - G. A. Wanner; C. J. Busch; B. Vollmar; M. D. Menger (Inflammation Research, 2004)

Evidence for Selection of more Adapted Human Immunodeficiency Virus Type 1 Recombinant Strains in a Dually Infected Transfusion Recipient - Luciana Jesus Costa; Allen J. Mayer; Michael P. Busch; Ricardo Sobhie Diaz (Virus Genes, 2004)

NHE-1 inhibition: from protection during acute ischaemia/reperfusion to prevention/reversal of myocardial remodelling - Wolfgang J. Linz; Andreas E. Busch (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Use of the firefly luciferase gene in a barley ( Hordeum vulgare ) transformation system - W. Harwood; S. Ross; S. Bulley; S. Travella; B. Busch; J. Harden; J. Snape (Plant Cell Reports, 2002)

Forest ecosystems and the changing patterns of nitrogen input and acid deposition today and in the future based on a scenario - Gerald Busch; Gerhard Lammel; Friedrich O. Beese; Johann Feichter; Frank J. Dentener; Geert-Jan Roelofs (Environmental Science and Pollution Research, 2001)

Influence of weather and climate on subjective symptom intensity in atopic eczema - E. Vocks; R. Busch; C. Fröhlich; S. Borelli; H. Mayer; J. Ring (International Journal of Biometeorology, 2001)

Density-dependent habitat selection between maize cropfields and their borders in two rodent species (Akodon azarae and Calomys laucha) of Pampean agroecosystems - Karina Hodara; María Busch; Marcelo J. Kittlein; Fernando O. Kravetz (Evolutionary Ecology, 2000)

Characterisation of oxidised 7Fe dicluster ferredoxins with NMR spectroscopy - Jonathan P. Hannan; Johanneke L. H. Busch; Jacques Breton; Richard James; Andrew J. Thomson; Geoffrey R. Moore; S. L. Davy (JBIC Journal of Biological Inorganic Chemistry, 2000)

KATP channel blocker HMR 1883 reduces monophasic action potential shortening during coronary ischemia in anesthetised pigs - K.J. Wirth; J. Uhde; B. Rosenstein; H.C. Englert; H. Gögelein; B.A. Schölkens; A.E. Busch (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Expression, functional characterization and tissue distribution of a Na + /H + exchanger cloned from Xenopus laevis oocytes (XL-NHE) - S. Busch; Dieter Rosskopf; Hans-J. Lang; Andreas Weichert; Winfried Siffert (Pflügers Archiv - European Journal of Physiology, 1998)

Effect of extracellular pH on the myo -inositol transporter SMIT expressed in Xenopus oocytes - J. Matskevitch; C. A. Wagner; T. Risler; H. M. Kwon; J. S. Handler; S. Waldegger; A. E. Busch; F. Lang (Pflügers Archiv - European Journal of Physiology, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Chloride Conductance and P i Transport are Separate Functions Induced by the Expression of NaPi-1 in Xenopus Oocytes - S. Bröer; A. Schuster; C.A. Wagner; A. Bröer; I. Forster; J. Biber; H. Murer; A. Werner; F. Lang; A.E. Busch (The Journal of Membrane Biology, 1998)

Electrophysiological Characterization of the Flounder Type II Na + /P i Cotransporter (NaPi-5) Expressed in Xenopus laevis Oocytes - I.C. Forster; C.A. Wagner; A.E. Busch; F. Lang; J. Biber; N. Hernando; H. Murer; A. Werner (The Journal of Membrane Biology, 1997)

K V LQT channels are inhibited by the K + channel blocker 293B - M. Bleich; M. Briel; A. E. Busch; H. J. Lang; U. Gerlach; H. Gögelein; R. Greger; K. Kunzelmann (Pflügers Archiv - European Journal of Physiology, 1997)

Lack of interaction between meloxicam and warfarin in healthy volunteers - D. Türck; C. A. P. F. Su; G. Heinzel; U. Busch; E. Bluhmki; J. Hoffmann (European Journal of Clinical Pharmacology, 1997)